Green supply chain management in manufacturing firms : A resource‐based viewpoint - Khan, Mehmood; Ajmal, Mian M.; Jabeen, Fauzia; Talwar, Shalini; Dhir, Amandeep (John Wiley & Sons, 2023)
As sustainability draws increasing attention due to the COVID-19 pandemic, interest in the green supply chain has likewise substantially increased. The present study contributes deeper insights into the logical integration of the resource-based characteristics that can facilitate the effective transition from traditional to green supply chains while also increasing the effectiveness of existing green supply chains. The proposed model, rooted in the resource-based view (RBV) theory, examines the associations of supply chain connectivity (SCC), supply chain information sharing (SCIS), top management commitment (TMC) and green procurement and logistics acceptance (GPLA) with green supply chain management (GSCM). Analysis of data from employees at 381 manufacturing firms in the United Kingdom confirmed the positive associations of SCC and SCIS with TMC and GPLA, of TMC with GPLA and GSCM and of GPLA with GSCM. The results also confirmed the serial mediation effect of TMC and GPLA on the associations of both SCC and SCIS with GSCM. The study offers several practical insights and theoretical contributions, including a novel GSCM scale.
Keywords: green supply chain management (GSCM); GSCM scale; manufacturing firm; resource-based view (RBV); UK; fi=Tuotantotalous|en=Industrial Management|